Malignant neoplasms ozone therapy - Pavel Yu. Andreev; Ivan P. Moshurov; Nataliya V. Korotkih; Viktoria V. Shishkina; Tatiana V. Samoilenko; Elena S. Goryushkina; Lyubov N. Antakova (RUDN Journal of Medicine, 2024)
The development of effective therapeutic approaches for the treatment of malignant neoplasms is one of the priorities of modern biomedical research. Disappointing data from epidemiological indicators and statistical calculations of morbidity dictate the need to develop and implement increasingly effective treatment methods, as well as its modulation. In experimental work on cell lines, animal models and in clinical studies, the positive biological effects of ozone therapy are noted, consisting in the ability of ozone to have an antineoplastic effect on tumors and sensitize them to chemoradiotherapy. Therapy of malignant tumors is a key object of modern biomedical studies. The aim of this work was to summarize experimental and clinical data on the place of ozone therapy in the treatment of malignant neoplasms. The literature included in the current systematic review was obtained from an independent literature search performed in the following databases: Elibrary, Сyberleninka, Central Scientific Medical Library, Google Scholar, Semantic Scholar, PubMed and Cochrane. It was found that the biological effects of ozone are based on its reactions with organic compounds: water-soluble and lipophilic antioxidants, as well as unsaturated fatty acids, resulting in the generation of reactive oxygen species and lipid peroxides, which have messenger properties, interacting with various cellular and tissue structures. It is believed that early biological effects are realized due to reactive oxygen species, and late ones due to lipoperoxides. Conclusion. In a number of research works, which were carried out on many cultures of tumor cells, animal models and in clinical use, the positive biological effects of ozone therapy were established, associated with the fact that ozone has a cytotoxic and cytostatic effect on cyclic histogenesis and localization, and also sensitizes blastotransformed cells to ionizing agents and chemotherapeutic agents.